ANALISIS PENGARUH KUALITAS KEBIJAKAN IDENTITAS KEPENDUDUKAN DIGITAL (IKD) BERBASIS DIGITAL TERHADAP KEPUASAN MASYARAKAT KOTA PADANG - Fajri Valentino; Rahmadani Yusran (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
The aim of this research is to evaluate the influence of the quality of Digital Identity Policy (IKD) on community satisfaction in Padang City. This research used a quantitative approach involving 100 respondents who were randomly selected from the population of IKD users in Padang City. To measure the impact of the quality of IKD policies on community satisfaction, data collection was carried out using a questionnaire based on a Likert scale. Data analysis was carried out using SPSS 25 for Windows which shows that there is a partially significant influence on the quality of IKD policies on community satisfaction. The significance value of 0.056 is less than 0.05 and the t-count value of 10.510 exceeds the t-table criterion of 3.880. This study provides important insights into the relationship between information technology policy implementation and public satisfaction with government administration. The implications of these findings include the need to improve information technology infrastructure and educate the public regarding the use of IKD to ensure the effectiveness and sustainability of efforts to improve the quality of public services. In conclusion, the quality of the Digital Identity Policy (IKD) is proven to have a significant impact on community satisfaction in Padang City.